Characteristics of Ethical Business Cultures - Ardichvili, Alexandre (Journal of business ethics, 2009)
The purpose of this study was to identify general characteristics attributed to ethical business cultures by executives from a variety of industries. Our research identified five clusters of characteristics: Mission- and Values-Driven, Stakeholder Balance, Leadership Effectiveness, Process Integrity, and Long-term Perspective. We propose that these characteristics be used as a foundation of a comprehensive model that can be engaged to influence operational practices in creating and sustaining an ethical business culture.